Diseño de un sistema de control Fuzzy para el manejo de una ortesis de la rodilla activa simula en un entorno 3D (2023)
The present comprehensive degree work develops a control system focused on the rehabilitation of the knee, the control is reflected in the monitoring of the angular movement. Said angular movement is observed thanks to the active orthosis designed and simulated in a 3D environment, this, with the future objective of creating a capable device in order to automate part of a complete rehabilitation therapy, specifically in passive therapy, which is where the patient needs external help to flex - extend the leg and gradually recover the range of motion. Normally, for any knee injury, a rehabilitation and recovery therapy plan is needed. To give a context of the problem about the lack of automation, we begin by describing a traditional knee rehabilitation therapy, initially the inflammation of the joint is reduced to start as soon as possible with small movements, the position of the patient depends on the professional manager since It can be sitting or lying down, but always looking for the comfort of both to be able to complete the primary exercises that are: Flexion and extension, this happens in passive kinesitherapy. Each time the arc of angular mobility must increase to observe an improvement, the ranges handled by physiotherapists go from 0-20°, 0-40°, 0-60°, 0-90° and the measurement of these angles is carried out by a tool called a goniometer. When inquiring into the rehabilitation process, we find that they do not use this tool and the recovery is subjective, since they depend on the reaction that is reflected in the patient to make decisions, that is, if they feel pain, they stop immediately with therapy until you can continue again. That is why the control system seeks to ensure the angle within the range of 0° to 90° and the movement can be observed in the active orthosis designed in 3D. For the design and development of the Fuzzy control system, the Matlab tool that goes hand in hand with the Simulink platform is used, this programming is done by means of blocks which will have input and output variables, that is why that other external microcontrollers are used for specific actions that will be seen in the development of this document. The active support orthosis is designed in a CAD program called SolidWorks, to then be taken to Simulink where the assembly is carried out in order to unify the entire control system and to be able to proceed with the manipulation. This is demonstrated in the results of the document.